2011
DOI: 10.1172/jci43853
|View full text |Cite
|
Sign up to set email alerts
|

Mouse ES and iPS cells can form similar definitive endoderm despite differences in imprinted genes

Abstract: The directed differentiation of iPS and ES cells into definitive endoderm (DE

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
50
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 41 publications
2
50
0
Order By: Relevance
“…While control cells grew as a uniform monolayer, SMARCD1-KD cells organized into two distinct morphological populations that differed by the expression of Nestin or GATA4 ( Figure 4I) in one sub-population and Lamininb1 or FOXA2 in the other ( Figures S4A and S4B). RAinduced, FOXA2-positive, SMARCD1-KD cells also showed elevated levels of KLF4 ( Figure S4B) and directed endodermal differentiation (Christodoulou et al, 2011) resulted in enhanced endodermal marker expression in the SMARCD1-KD clones compared with WT ( Figure S4C). We thus tested whether the increased KLF4 levels in these cells may explain the perturbed differentiation phenotypes by repeating these experiments under low-KLF4 conditions using infection with KLF4-specific shRNAs.…”
Section: Smarcd1 Is Necessary For Proper Esc Differentiationmentioning
confidence: 99%
“…While control cells grew as a uniform monolayer, SMARCD1-KD cells organized into two distinct morphological populations that differed by the expression of Nestin or GATA4 ( Figure 4I) in one sub-population and Lamininb1 or FOXA2 in the other ( Figures S4A and S4B). RAinduced, FOXA2-positive, SMARCD1-KD cells also showed elevated levels of KLF4 ( Figure S4B) and directed endodermal differentiation (Christodoulou et al, 2011) resulted in enhanced endodermal marker expression in the SMARCD1-KD clones compared with WT ( Figure S4C). We thus tested whether the increased KLF4 levels in these cells may explain the perturbed differentiation phenotypes by repeating these experiments under low-KLF4 conditions using infection with KLF4-specific shRNAs.…”
Section: Smarcd1 Is Necessary For Proper Esc Differentiationmentioning
confidence: 99%
“…Therefore, using TargetScan, we searched for predicted targets of mmu-miR-141 focusing on two pathways related to b-cell function, insulin signaling and maturity onset diabetes of the young (MODY), and narrowed down the list to three genes: Cbl, FoxA2, and Mnx1 (also known as Hb9). Using a data set on gene expression arrays comparing iPSCs and iPSC-derived endoderm (GSE27087) (Christodoulou et al, 2011), we found a correlation between mmu-miR-141 expression and target downregulation for two of the three genes, Cbl (log fold-change iPSCs/iPSC-derived endoderm = À0.080, p = 0.16) and FoxA2 (logFC iPSCs/iPSC-derived endoderm = À1.68, p = 5.11 Â 10 À6 ); however, Mnx1 was not included in the microarray. While these genes contain 3 0 UTR binding sequences for mmu-miR-141, luciferase reporter assays would be necessary to validate them as targets.…”
Section: Analysis Of Activin-a-induced Upregulated Mirnas In Mature Ementioning
confidence: 99%
“…During the course of these studies, Shinya Yamanaka's Nobel Prize-winning discovery was published, describing how to induce pluripotency in somatic cells via the overexpression of Oct4, Klf4, Sox2, and cMyc (7). The reprogrammed cells, induced pluripotent stem cells (iPSCs), are remarkably similar to ESCs (8). We compared ESCs with iPSCs in terms of their functional potential to form definitive endoderm in vitro and found that Nodal signaling induced functionally similar definitive endoderm from either ESCs or iPSCs, despite very subtle differences in the global transcriptomes of the endodermal cells derived from these two types of pluripotent stem cells (PSCs) (8,9).…”
mentioning
confidence: 99%
“…The reprogrammed cells, induced pluripotent stem cells (iPSCs), are remarkably similar to ESCs (8). We compared ESCs with iPSCs in terms of their functional potential to form definitive endoderm in vitro and found that Nodal signaling induced functionally similar definitive endoderm from either ESCs or iPSCs, despite very subtle differences in the global transcriptomes of the endodermal cells derived from these two types of pluripotent stem cells (PSCs) (8,9). To this day we and others have continued to find that the same recipes that differentiate ESCs into endodermal lineages work similarly to differentiate iPSCs.…”
mentioning
confidence: 99%